Latinx college students' anxiety, academic stress, and future aspirations: the role of sibling relationship quality. - Fernandez, Lorena R.; Girón, Sonia E.; Killoren, Sarah E.; Campione-Barr, Nicole (Journal of Child & Family Studies, 2023)
Latinx students experience stress at higher rates than European-American college-students in the U.S. and report the highest levels of anxiety among all other college-students, which can be a potential barrier to success. However, family members are identified as important sources of support by Latinx young-adults, and feeling support from family indicates a higher likelihood to remain enrolled in college. Few studies have explored the role of siblings in this relationship. This study examined whether positive and negative relationship qualities (RQ) between Latinx siblings may interact with level of anxiety, predicting academic stress (AS) and future aspirations (FA). Findings indicated that younger siblings with high anxiety and high negative RQ experienced higher levels of AS, while older siblings with low or mean-level anxiety and high negative RQ experienced high AS. Younger siblings with low anxiety, and high negative RQ with older siblings experienced low FA. The findings provide evidence that sibling relationship quality in Latinx students moderates the associations with anxiety, academic stress, and future aspirations, and that the presence of negative relationship qualities carried particular implications for future aspirations and academic stress. Understanding the influence of Latinx sibling RQ on mental health and AS can offer insight into the role of sibling relationships in the context of health, academic retention, and success in Latinx young people. Highlights: Examined if relationship qualities between Latinx siblings interact with anxiety, academic stress, and future aspirations. The presence of negative relationship qualities carries particular implications for future aspirations and academic stress Younger siblings with high anxiety and high negative relationship qualities experienced higher levels of academic stress. The higher the positive sibling relationship quality, the higher the future aspirations. Understanding influences of Latinx sibling relationships on mental health and academics can guide university efforts.